Implementation of Good Governance in Digital-Based Public Services in Local Government - Ivan Dicksan (Jurnal Ragam Pengabdian, 2026)
The implementation of good governance has become increasingly significant in the era of digital transformation, particularly within local government public services. Digital-based public services are expected not only to enhance administrative efficiency but also to strengthen governance principles such as transparency, accountability, participation, effectiveness, efficiency, and rule of law. This study aims to analyze the implementation of good governance principles in digital-based public services at the local government level, identify enabling and constraining factors, and examine their implications for service quality and institutional performance. The research employs a qualitative approach using a systematic literature review design. Data were collected from peer-reviewed journal articles, academic books, and official policy documents related to digital governance and public administration. Content analysis was applied through data reduction, thematic categorization, and interpretative synthesis. The findings indicate that digital transformation in local governments has significantly enhanced transparency, accountability, and service responsiveness. However, challenges such as digital inequality, system fragmentation, cybersecurity risks, and limited institutional capacity continue to constrain substantive governance reform. Sustainable improvement requires integrated digital architecture, leadership commitment, regulatory coherence, and inclusive digital policies.